2006
DOI: 10.1110/ps.051751706
|View full text |Cite
|
Sign up to set email alerts
|

High resolution structure of the HDGF PWWP domain: A potential DNA binding domain

Abstract: Hepatoma Derived Growth Factor (HDGF) is an endogenous nuclear-targeted mitogen that is linked with human disease. HDGF is a member of the weakly conserved PWWP domain family. This 70-amino acid motif, originally identified from the WHSC1 gene, has been found in more than 60 eukaryotic proteins. In addition to the PWWP domain, many proteins in this class contain known chromatin remodeling domains, suggesting a role for HDGF in chromatin remodeling. We have determined the NMR structure of the HDGF PWWP domain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 50 publications
(61 reference statements)
8
101
0
Order By: Relevance
“…The domain is often associated with chromatin function, including histone and DNA modification, transcription, and DNA repair (41). Although several publications indicate that the PWWP domain recognizes chromatin and DNA without sequence specificity (43,83), Yang and Everett (45) demonstrated that HDGF acts as a transcriptional repressor through binding of its PWWP element to a conserved DNA element in the promoter of target genes, including the SMYD1 gene. We and others demonstrated that fusion of alternative DNA-binding proteins to the C-terminal end of LEDGF/p75 allows retargeting of integration in the neighborhood of the respective protein binding sites (17,18).…”
Section: H2azmentioning
confidence: 99%
See 1 more Smart Citation
“…The domain is often associated with chromatin function, including histone and DNA modification, transcription, and DNA repair (41). Although several publications indicate that the PWWP domain recognizes chromatin and DNA without sequence specificity (43,83), Yang and Everett (45) demonstrated that HDGF acts as a transcriptional repressor through binding of its PWWP element to a conserved DNA element in the promoter of target genes, including the SMYD1 gene. We and others demonstrated that fusion of alternative DNA-binding proteins to the C-terminal end of LEDGF/p75 allows retargeting of integration in the neighborhood of the respective protein binding sites (17,18).…”
Section: H2azmentioning
confidence: 99%
“…The domain is present in diverse chromatin-associated proteins involved in DNA repair, histone modification, transcriptional regulation, and DNA methylation (41)(42)(43). Although the function of the domain is unknown, the PWWP module has been reported to bind DNA without sequence specificity (41,44) and to have methyllysine binding ability (39,40).…”
mentioning
confidence: 99%
“…30 Additionally, we have also identified a PWWP-domain (proline-tryptophan-tryptophan-proline) which is approximately 70 amino acids in length and is believed to interact nonspecifically with DNA. 40 Bromodomains are found in a variety of mammalian, invertebrate and yeast DNA-binding proteins, and are able to interact with acetylated lysine on histone proteins. Indeed, a point-mutation of conserved tyrosine residues in the bromodomains of the yeast protein Bdf1 abolishes binding to acetylated histones H3 and H4.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several three-dimensional structures of PWWP domains have been reported, including those of DNMT3a, DNMT3b, Pdp1, Pdp2, HDGF, HDGF2, HDGF-related protein 3 (HRP-3), Bromo and plant homeodomain (PHD) finger-containing protein 1 (BRPF1), BRPF2, BRPF3, LEDGF/ p75, Mutated melanoma-associated antigen 1 (MUM1), MutS homolog 6 (MSH6), and Zinc finger MYND domaincontaining protein 11 (ZMNYD11) (Qiu et al 2002;Slater et al 2003;Sue et al 2004Sue et al , 2007Nameki et al 2005;Lukasik et al 2006;Laguri et al 2008;Vezzoli et al 2010;Wu et al 2011;Eidahl et al 2013;van Nuland et al 2013;Wang et al 2014;Wen et al 2014). Table 1 summarizes the structural data currently available in the literature.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%
“…The PWWP domains of DNMT3a/b contain a bundle of five α-helices (Qiu et al 2002;Wu et al 2011). On the other hand, those of BRPF1, HDGF, HDGF2, and Pdp1 are composed of two α-helices connected by a loop (Lukasik et al 2006;Vezzoli et al 2010;Wu et al 2011;Qiu et al 2012). Recently, the structure of the PWWP domain from LEDGF/ p75 revealed a C-terminal region with less helical content than its counterparts.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%